Fertilización de híbridos de maíz (Zea mays L.) con fertilizantes compuestos, en la provincia de santo Domingo de los Tsachilas. - Chungata Aguilar, Henry Hernán (2014)
This research was conducted during the rainy season of 2013, at the "Los Laureles" located at km 37 via Santo Domingo Quevedo in San Vicente del Nila Community of the Province of Santo Domingo de los Tsachilas. Study endpoints were to evaluate the agronomic performance of corn hybrids (Zea mays L.) with fertilizer compounds, determine the grain yield of hybrids in study versus compound fertilizer; compound fertilizer obtained suitable for excellent performance in grain hybrids and finally study the benefit-cost analysis of the treatments under study. Corn hybrids evaluated were: lNlAP H-553, THUNDER NB 7443 and DK 1596 were NPK compound fertilizer, COMPLETE, DOUBLE WIN (commercial compound) and WITNESS simple fertilizer (Urea 46% N). The experimental design was Split plots with three replications, being constituted the main plot of corn hybrids and fertilizer subplots mentioned. The experimental plot consisted of six rows of eight meters in length at a distance of 0.80 m apart and between strokes of 0.20 m...............................................